Distinct etiologies of high-sensitivity troponin T elevation predict different mortality risks for patients hospitalized with COVID-19. (15th March 2022) - Khaloo, Pegah; Shaqdan, Ayman; Ledesma, Pablo A.; Uzomah, Uwajachukwumma A.; Galvin, Jennifer; Ptaszek, Leon M.; Ruskin, Jeremy N.
Abstract: Background: Cardiovascular events in the context of COVID-19 infection increase the risk of negative patient outcomes, but large cohort studies describing this association are limited. The purpose of the current study was to investigate the potential associations between cardiovascular events and mortality in patients hospitalized due to COVID-19. Methods: A retrospective chart review was performed in 2450 patients hospitalized for confirmed COVID-19 infection within a single hospital network between March 15 and June 15, 2020. Logistic regression analysis was used to identify predictors of mortality. Results: In the study population, 57% of patients had elevated high sensitivity troponin (hs-TnT) levels. Acute heart failure occurred in 23% of patients and arrhythmias were observed in 8% of patients. Of the 1401 patients with elevated hs-TnT levels, a primary cardiac etiology (e.g., myocardial infarction) was identified in 653 (47%) patients. In the remaining 748 (53%) patients, there was evidence of a primary non-cardiac etiology for hs-TnT elevation such as renal failure ( n  = 304) and critical illness ( n  = 286). Elevated hs-TnT was associated with increased risk of mortality. A significantly higher mortality rate was observed for hs-TnT elevation associated with a primary cardiac etiology (OR 4.6, 95% CI: 2.7–7.6; P  < 0.001) than a primary non-cardiac etiology (OR 2.7, 95% CI: 1.6–4.5; P < 0.001). Conclusions: Elevated hs-TnT in the context of COVID-19 infection is associated with a significantly increased mortality risk. Hs-TnT elevation in the context of a primary cardiac etiology confers a nearly 2-fold higher mortality risk than hs-TnT elevation due to a primary non-cardiac etiology. Highlights: Elevated hs-TnT in the context of COVID-19 infection increases risk of mortality. Mortality risk is highest for hs-TnT elevation due to a primary cardiac problem. Evidence of ventricular dysfunction on TTE increases mortality in COVID-19.